The chosen ones : a novel - Sem-Sandberg, Steve, 1958- (Farrar, Straus and Giroux, 2016)
"The Am Spiegelgrund clinic, in glittering Vienna, masqueraded as a well-intentioned reform school for wayward boys and girls and a home for chronically ill children. The reality, however, was very different: in the wake of Germany's annexation of Austria on the eve of World War II, its doctors, nurses, and teachers created a monstrous parody of the institution's benign-sounding brief. The Nazi regime's euthanasia program would come to determine the fate of many of the clinic's inhabitants. Through the eyes of a child inmate, Adrian Ziegler, and a nurse, Anna Katschenka, Steve Sem-Sandberg, the author of the award-winning The Emperor of Lies, explores the very meaning of survival. An absorbing, emotionally overwhelming novel, rich in incident and character, The Chosen Ones is obliquely illuminated by the author's sharp sense of the absurd. Passionately serious, meticulously researched, and deeply profound, this extraordinary and dramatic novel bears witness to oppression and injustice, and offers invaluable and necessary insight into an intolerable chapter in Austria's past"--